The cycles of constitutional time - Balkin, J. M. (New York, NY : Jack Balkin, 2020)
'The Cycles of Constitutional Time' shows where American democracy has been and projects where it is going. Jack Balkin explains why our politics seems so dysfunctional and why fights over the courts seem so bitter and unhinged. He portrays our present troubles in terms of longer, constitutional trends. In doing so, he also offers a message of hope for the future. The same trends that put us in this predicament are slowly changing. Our political system can get better if Americans mobilize to change it.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 25, 2020).
Keywords: Constitutional law -- Political aspects -- United States; United States -- Politics and government -- 2017-; Law; Laws of specific jurisdictions & specific areas of law